High-sensitive Troponin T increase after exercise in patients with pulmonary arterial hypertension - Völkers, Mirko; Rohde, David; Zelniker, Thomas; Weiss, Celine; Giannitsis, Evangelos; Katus, Hugo; Meyer, Franz Joachim (BMC pulmonary medicine, 2013)
The current study aimed to investigate the release of myocardial high-sensitive Troponin T (hsTnT) in patients with pulmonary arterial hypertension (PAH) in response to maximal physical exercise.